Neurosyphilis in AIDS patient presenting as isolated cranial nerve 6 palsy. Issue 10 (26th June 2020) - Singh, Sanjay; Puranik, Priyangi; Lin, Ethan; Marti, Miriam; Liu, Antonio
Abstract: Early neurosyphilis can occur in an immunocompromised host. It has a widely varied presentation. Isolated CN6 as presenting symptom has not been described. Abstract : Early neurosyphilis can occur in an immunocompromised host. It has a widely varied presentation. Isolated CN6 as presenting symptom has not been described.